ANALISIS LITERASII KEUANGAN SYARIAH PADA GENERASI Z SMAS AL-IHSAN DESA PERTUMBUKAN - Ocha Pratika; Chindy Jihan Najiyah; Febrianti Shakira; Syaiful Amri (LPPM ITB AAS Indonesia Surakarta, 2025)
The low level of Islamic financial literacy in Indonesia is a serious problem. This situation reflects the need for more intensive educational efforts, especially for the younger generation. In response to this challenge, concrete steps are needed to increase their understanding and awareness of the Islamic financial system. This Community Service Program (KKN) team aims to increase students' understanding and awareness of the importance of Islamic financial literacy among Generation Z through an educational and participatory approach. The program is implemented by students from the State Islamic University of North Sumatra at Al-Ihsan Senior High School in Pertumbungan Village using the method Participatory Action Research (PAR), which emphasized active involvement between students, the school, and participants. The material presented covered the legal basis of Islamic banking, the history and development of Islamic banking in Indonesia, the differences between Islamic and conventional banks, and modern financial issues such as the dangers of online loans, online gambling, and the importance of saving from an early age. The results of the activity demonstrated high enthusiasm from students who actively participated in discussions and quizzes, with most participants able to understand the basic concepts of Islamic finance and differentiate it from conventional systems. Evaluations showed that this activity was effective in raising students' awareness of Islamic values ​​in financial management and fostering a critical attitude towards financial practices that conflict with Islamic principles. In addition to providing knowledge, this activity also strengthened the relationship between the campus and the community. It is recommended that it be continued with a broader scope, involving the general public and MSMEs for a more equitable and sustainable impact. Keywords: Islamic Financial Literacy, Islamic Financial Institutions, Generation Z, Digital Technology